THE INFLUENCE OF SERVICE QUALITY AND CUSTOMER TRUST ON CUSTOMER SATISFACTION AT PT. PLN PERSERO, KENDARI CITY AREA - Azis Muthalib, Dzulfikri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyse the effect of service quality and customer trust on customer satisfaction. Service quality is measured through the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, while customer trust is measured based on the aspects of honesty, benevolence, and competence. The method used is a quantitative approach with multiple regression analysis techniques. Research data was collected through a questionnaire distributed to 55 customer respondents. The results showed that service quality had a positive and significant effect on customer satisfaction, indicating that the better the customer's perception of service reliability and responsiveness, the higher the level of satisfaction felt. Customer trust was found to have a positive and significant effect on customer satisfaction. This means that when customers feel that the service is honest, transparent, and consistent, their level of satisfaction increases. The practical implication of this study is that it is necessary to continuously improve service quality standards and maintain transparency and accountability in order to strengthen customer trust, thereby achieving long-term satisfaction and loyalty.